Home-Made Simple Experiment to Measure Sound Intensity using Smartphones - Nuryantini, Ade Yeti; Zakwandi, Rizki; Ariayuda, Muhamad Ari (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
The researchers present a simple experimental activity to measure the sound intensity level using an Android-based smartphone to prove the inverse square law and analyze the dependence of the sound intensity to the sound source frequency. The type of this study was quantitative research by conducting level of intensity experiment using a pair of smartphones with one smartphone functioning as the sound source using a tone generator free application (app) and the other smartphone functioning as the detector installed with Physics Toolbox sound meter application to measure the arriving sound intensity level. The smartphone functioning as the sound source was placed at a certain place labeled as the origin point (0.0), while the other smartphone as the detector was placed at various distances on the x-axis. In this study, the frequencies of the tone generator used were 500 Hz, 1000 Hz, and 2000 Hz. Then, the sound intensity level versus distance was analyzed to determine the compatibility between the experimental results using a smartphone and the prevailing theory, namely the inverse square model. The sound intensity level detected by the smartphone from 2,000 Hz resulted in the graph with smaller slope after passing 0.3 meters. The results follow the theorem of which the sound intensity level at the detector depends on the distance between the source and the detector based on the inverse square law. When the frequency of a source was changed (500 Hz, 1000 Hz and 2000), the sound intensity also changed. Higher frequency leads to a larger sound intensity. The experiment can thus be used to assist  high school students and physics undergraduates in understanding the inverse square law of sound or to study environmental noise with a simple and low-cost experiment.